Comparison of the precursor, amino acid oxidation, and end-product methods for the evaluation of protein turnover in senior dogs - Pacheco, Letícia G. [UNESP]; Goloni, Camila [UNESP]; Di Santo, Ludmilla G. [UNESP]; Scarpim, Lucas B. [UNESP]; Eugênio, Débora A. [UNESP]; Castro, Ariel de [UNESP]; Costa, Vladimir E. [UNESP]; Carciofi, Aulus C. [UNESP] (Public Library of Science (PLoS), 2024)
Stable isotope methods have been used to study protein metabolism in humans; however, there application in dogs has not been frequently explored. The present study compared the methods of precursor (13C-Leucine), end-products (15N-Glycine), and amino acid oxidation (13C-Phenylalanine) to determine the whole-body protein turnover rate in senior dogs. Six dogs (12.7 ± 2.6 years age, 13.6 ± 0.6 kg bodyweight) received a dry food diet for maintenance and were subjected to all the above-mentioned methods in succession. To establish 13C and 15N kinetics, according to different methodologies blood plasma, urine, and expired air were collected using a specifically designed mask. The volume of CO2 was determined using respirometry. The study included four methods viz. 13C-Leucine, 13C-Phenylalanine evaluated with expired air, 13C-Phenylalanine evaluated with urine, and 15N-Glycine, with six dogs (repetitions) per method. Data was subjected to variance analysis and means were compared using the Tukey test (P<0.05). In addition, the agreement between the methods was evaluated using Pearson correlation and Bland-Altman statistics. Protein synthesis (3.39 ± 0.33 g.kg-0,75. d-1), breakdown (3.26 ± 0.18 g.kg-0.75.d-1), and flux estimations were similar among the four methods of study (P>0.05). However, only 13C-Leucine and 13C-Phenylalanine (expired air) presented an elevated Pearson correlation and concordance. This suggested that caution should be applied while comparing the results with the other methodologies.